The Influence of Differences in Solvents and Concentration on the Efficacy of Propofol at Induction of Anesthesia - Yukako Obata; Yushi U. Adachi; Katsumi Suzuki; Taiga Itagaki; Hiromi Kato; Maiko Satomoto; Yoshiki Nakajima (Anesthesiology Research and Practice)
Background. Propofol is a popular intravenous anesthetic and varieties of formulations were produced from different laboratories. The present study compared efficacy of propofol of different laboratories and different concentrations (1 and 2%) during induction of anesthesia. Methods. Seventy-five scheduled surgical patients were randomly allocated into three groups. The patients of group D1 received AstraZeneca Diprivan 1% (Osaka, Japan) at a rate of 40 mg kg−1 h−1. Group M1 was given 1% Maruishi (Maruishi Pharmaceutical, Osaka, Japan) and group M2 was given 2% formulation at the same rate of propofol. Achieving hypnosis was defined as failure to open their eyes in response to a verbal command and the venous blood sample was withdrawn. Results. The hypnotic doses of M2 were significantly larger (D1: 91.4±30.9, M1: 90.7±26.7, and M2: 118.4±40.2 mg, resp. (mean ± SD). p<0.005). Age and gender were selected as statistically significant covariates using general linear model-ANOVA. The blood concentration showed no significant difference among the groups (3.73±2.34, 4.10±3.04, and 4.70±2.12 μg mL−1, resp.). Conclusion. The required dose of propofol was different among the formulations; however, the serum concentration showed no significant difference. This trial is registered with UMIN Clinical Trial Registry: UMIN000019925.